METHODS FOR THE PREVENTION AND TREATMENT OF SEPSIS IN PATIENTS WITH DIABETES MELLITUS - K.J. Matmurotov; S.S Xudayorov; I.Y Yakubov; U.G. Voxidov (Journal of modern medicine, 2026)
Diabetes mellitus is an important risk factor for the development of infectious complications, particularly diabetic foot infections, purulent-necrotic soft tissue infections, and sepsis. Hyperglycemia, micro- and macroangiopathy, peripheral neuropathy, reduced tissue perfusion, and delayed wound healing create favorable conditions for a severe course of infection.Objective. To evaluate a comprehensive strategy for the prevention and treatment of sepsis in patients with diabetes mellitus and to statistically compare clinical and laboratory outcomes between the main and comparison groups.Materials and Methods. The study included 130 patients observed during the period 2023–2026. Of these, 85 patients treated in 2025–2026 constituted the main group, while 45 patients treated in 2023–2024 constituted the comparison group. Intergroup analysis of clinical, laboratory, and outcome parameters was planned using percentages, mean values, the χ² test, and Fisher’s exact test. The numerical results presented in this document are modeled statistical examples.